Development and application of high temperature high performance liquid chromatography to the analysis of pesticides and persistant organic pollutants - Sanagi, Mohd. Marsin; Wan Ibrahim, Wan Aini; Abu Naim, Ahmedy; Md. Saleh, Noorashikin; Norfairulzukry, Norfairul (Faculty of Science, 2008)
A high temperature reversed-phase liquid chromatography (RP-LC) method has been developed to separate polycyclic aromatic hydrocarbons (PAHs) on ODS-silica stationary phase using various proportions of organic modifier in the mobile phase. The selectivity and retention patterns of four PAHs (naphthalene, fluorene, phenanthrene and fluoranthene) were investigated on a Hypersil ODS-silica column (4.6 mm ID × 100 mm, 5 µm) with ultraviolet detection at 254 nm. Excellent separations for the PAHs were achieved with acetonitrile-water 40:60 (v/v) as the mobile phase at a flow rate of 2.5 mL/min at column temperatures ranging from 25°C to 70°C. Pressurized liquid extraction (PLE) method was also developed to determine the quantity of the PAHs in soil samples. It was found that PLE could reduce sample preparation time and reduce organic solvent consumption to one-fifth of that required by Soxhlet extraction (United States Environmental Protection Agency, (US EPA) Method 3545). With dichloromethane-acetone 50:50 (v/v) as the extraction solvent, the optimum conditions were found to be 180°C at a pressure of 250 bar. For the extraction of spiked PAHs, it was found that PLE gave results that are comparable to or better than those obtained by Soxhlet extraction with highest recoveries of fluoranthene 94.4% for PLE and 73.6% for Soxhlet extraction. The developed high-temperature RP-LC method gave limits of detection (LOD) for the PAHs in the range of 0.60 to 1.08 ppm.